Characterization of Human Influenza Virus Variants Selected In Vitro in the Presence of the Neuraminidase Inhibitor GS 4071 - Tai, Chun Y. (American Society for Microbiology, 1998)
An oral prodrug of GS 4071, a potent and selective inhibitor of influenza neuraminidases, is currently under clinical development for the treatment and prophylaxis of influenza virus infections in humans. To investigate the potential development of resistance during the clinical use of this compound, variants of the human influenza A/Victoria/3/75 (H3N2) virus with reduced susceptibility to the neuraminidase inhibitor GS 4071 were selected in vitro by passaging the virus in MDCK cells in the presence of inhibitor. After eight passages, variants containing two amino acid substitutions in the hemagglutinin (A28T in HA1 and R124M in HA2) but no changes in the neuraminidase were isolated. These variants exhibited a 10-fold reduction in susceptibility to GS 4071 and zanamivir (GG167) in an in vitro plaque reduction assay. After 12 passages, a second variant containing these hemagglutinin mutations and a Lys substitution for the conserved Arg292 of the neuraminidase was isolated. The mutant neuraminidase enzyme exhibited high-level (30,000-fold) resistance to GS 4071, but only moderate (30-fold) resistance to zanamivir and 4-amino-Neu5Ac2en, the amino analog of zanamivir. The mutant enzyme had weaker affinity for the fluorogenic substrate 2′-(4-methylumbelliferyl)-α-d-N-acetylneuraminic acid and lower enzymatic activity compared to the wild-type enzyme. The viral variant containing the mutant neuraminidase did not replicate as well as the wild-type virus in culture and was 10,000-fold less infectious than the wild-type virus in a mouse model. These results suggest that although the R292K neuraminidase mutation confers high-level resistance to GS 4071 in vitro, its effect on viral virulence is likely to render this mutation of limited clinical significance.